1992
DOI: 10.1139/y92-184
|View full text |Cite
|
Sign up to set email alerts
|

Differences in myocardial ischemic tolerance between 1- and 7-day-old rabbits

Abstract: Between 1 and 7 days of life, the newborn rabbit heart shifts from predominantly using carbohydrates to predominantly using fatty acids as an energy substrate. We therefore used isolated working hearts from 1- or 7-day-old rabbits to determine the effects of fatty acids on myocardial glucose use and the ability of hearts to recover following various periods of transient no-flow ischemia. One-day-old hearts were perfused via the inferior vena cava and ejected buffer through the cannulated aorta and pulmonary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Cellular metabolism in the heart is dynamic at different stages of cardiac myocytes. Glycolysis and fatty acid oxidation change from fetal to mature tissue (50). Pfkfb2 has been reported to play a special role in regulating glycolysis and proliferation in pancreatic cancer cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular metabolism in the heart is dynamic at different stages of cardiac myocytes. Glycolysis and fatty acid oxidation change from fetal to mature tissue (50). Pfkfb2 has been reported to play a special role in regulating glycolysis and proliferation in pancreatic cancer cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…76,83,84 Despite this increase in fatty acid levels, fatty acid oxidation rates remain low in the immediate newborn period, providing less than 15% of the heart's ATP requirements, 82,85 due in part to an inhibition of mitochondrial fatty acid uptake. 36,65,86,87 Within days of birth, a dramatic increase in fatty acid b-oxidation occurs (a 10-fold increase), which is accompanied by a parallel decrease in glycolytic rates. 82 Studies in newborn pigs have also shown an increase in fatty acid oxidation with age.…”
Section: Metabolic Phenotype In the Newborn And Neonatal Heartmentioning
confidence: 99%
“…Following ischemia, the presence of increased fatty acid oxidation rates is thought to result in a reduction in glucose oxidation via inhibition of the pyruvate dehydrogenase complex [4,7]. These low rates of glucose oxidation, relative to rates of glycolysis, contribute to poor cardiac efficiency during reperfusion, secondary to the production of protons from glycolysis uncoupled from glucose oxidation [19]. Proton clearance from the myocytes redirects ATP away from contractile function resulting in a decrease in cardiac efficiency.…”
Section: Discussionmentioning
confidence: 99%